Mixed convection flow at the lower stagnation point of a circular cylinder embedded in a porous medium filled by a nanofluid containing gyrotactic microorganisms - Leony Tham Yew Seng,; Roslinda Nazar,; Ioan Pop, (Penerbit Universiti Kebangsaan Malaysia, 2012)

(untitled)
In this paper, the steady mixed convection boundary layer flow near the lower stagnation point of a horizontal circular cylinder with a constant surface temperature embedded in a porous medium saturated by a nanofluid containing gyrotactic microorganisms in a stream flowing vertically upwards for both cases of a heated and cooled cylinder, is studied numerically. The resulting system of nonlinear ordinary differential equations is solved numerically using an implicit finite-difference scheme known as the Keller box method. By considering the governing parameters, namely the mixed convection parameter λ, the bioconvection Lewis number Lb, the traditional Lewis number Le, the bioconvection Péclet number Pb, the buoyancy ratio Nr, the bioconvection Rayleigh number Rb, the Brownian motion Nb and the thermophoresis Nt, the numerical results are obtained and discussed for the skin friction coefficient, the local Nusselt number, the local Sherwood number, the local density number of the motile microorganisms as well as the velocity, temperature, nanoparticles volume fraction and motile microorganisms density profiles.